The impact of skin decontamination on the time window for effective treatment of percutaneous VX exposure. (1st April 2017) - Joosen, M.J.A.; van den Berg, R.M.; de Jong, A.L.; van der Schans, M.J.; Noort, D.; Langenberg, J.P.
Abstract: The main goal of the present study was to obtain insight into depot formation and penetration following percutaneous VX poisoning, in order to identify an appropriate decontamination window that can enhance or support medical countermeasures. The study was executed in two phases, using the hairless guinea pig as an animal model. In the first phase the effect of various decontamination regimens on levels of free VX in skin and plasma were studied as well as on blood cholinesterase levels. Animals were exposed to 0.5 mg/kg VX and were not decontaminated (control), decontaminated with RSDL once at 15 or 90 min after exposure or three times at 15, 25 and 35 (10-min interval) or 15, 45 and 75 min after exposure (30-min interval). There was no significant effect of any of the decontamination regimens on the 6-h survival rate of the animals. However, all animals that had been decontaminated 15 min after exposure, showed a survival rate of more than 90%, compared to 50–60% in animals that were not decontaminated or decontaminated at 90 min after exposure. In the second phase of the study, hairless guinea pigs were exposed to 1 mg/kg VX on the shoulder, followed either by decontamination with RSDL (10 min interval), conventional treatment on indication of clinical signs or a combination thereof. It appeared that a thorough, repeated decontamination alone could not save the majority of the animals. A 100% survival rate was observed in the group that received a combination of decontamination and treatment. In conclusion, the effects of VX exposure could be influenced by various RSDL decontamination regimens. The results in freely moving animals showed that skin decontamination, although not fully effective in removing all VX from the skin and skin depot is crucial to support pharmacological intervention. Highlights: Skin levels of VX after dermal exposure were influenced by RSDL decontamination. Delayed RSDL decontamination up to 15 min is effective. Repetition of decontamination can improve residual VX levels. Effective decontamination has to be supported by follow up pharmacological intervention.